PENYULUHAN TENTANG HIFDZ AL-NASL DALAM PENINGKATAN EKONOMI KELUARGA PADA WARGA TERDAMPAK PENDEMI MELALUI USAHA TERNAK KAMBING - Soni Zakaria; Agus Supriadi (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2022)
Purpose of the study: Assisting the implementation of Hifdz al-Nasl in a contemporary sense through community empowerment by increasing the economy through goat farming. Methodology: In this study, the methods used are mentoring which includes socialization, counseling, practice, monitoring, and evaluation. Main Findings: During the service process, it was found that kindergarten ABA 37 students have not fully practiced the value of giving alms in everyday life and still need to be motivated to do so. Applications of this study: partners understand how important it is to implement Hifdz al-Nasl and be able to develop a business through goats as additional income. Novelty/Originality of this study: In this service, we have been able to identify the problems experienced by pertners by using socialization, counseling, practice, monitoring, and evaluation, expected the present of an improvement on the economy of partner families and can implement family resilience in the midst of the economic crush due to Covid-19.